2020
DOI: 10.1186/s40814-019-0544-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the nomenclature, methodology, and reporting of studies that review methods: a pilot methodological review

Abstract: Background: A relatively novel method of appraisal, methodological reviews (MRs) are used to synthesize information on the methods used in health research. There are currently no guidelines available to inform the reporting of MRs. Objectives: This pilot review aimed to determine the feasibility of a full review and the need for reporting guidance for methodological reviews. Methods: Search strategy: We conducted a search of PubMed, restricted to 2017 to include the most recently published studies, using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…While the latter two risks exist in methodological research, the negative consequences may be substantially less than for clinical outcomes. In a sample of 31 methodological studies, 7 (22.6%) referenced a published protocol [9]. In the Cochrane Library, there are 15 protocols for methodological reviews (21 July 2020).…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the latter two risks exist in methodological research, the negative consequences may be substantially less than for clinical outcomes. In a sample of 31 methodological studies, 7 (22.6%) referenced a published protocol [9]. In the Cochrane Library, there are 15 protocols for methodological reviews (21 July 2020).…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%
“…The term "review" may point towards an appraisal or "review" of the design, conduct, analysis or reporting (or methodological components) of the targeted research reports, yet it has also been used to describe narrative reviews [41,42]. The term "survey" is also in line with the approaches used in many methodological studies [9], and would be indicative of the sampling procedures of this study design. However, in the absence of guidelines on nomenclature, the term "methodological study" is broad enough to capture most of the scenarios of such studies.…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This enterprise is registered on the EQUA-TOR network as the METhodological Review reportIng Checklist [4]. We have recently conducted a pilot study on a sample of methodological papers from 2017 and have identified many concerns, some of which were also raised in Dr. Puljak's letter and related commentary (e.g., issues with classification, reporting of sampling methods, and search strategies) [5].…”
Section: A Call For Consensus Guidelines On Classification and Reporting Of Methodological Studiesmentioning
confidence: 99%
“…Inspired by the IMPRINT review of reporting standards in prospective trials on infertility, this study aims to systematically review the methodological quality of published, largely retrospective studies on mTESE approaches and outcomes. Methodological analyses are designed to synthesize, analyze, and report on primary and secondary research and are highly useful in being able to demonstrate trends and inconsistencies in data reporting 15 . As noted by Li et al (2011), methodologic analysis also allows for identification of key areas of bias among non‐randomized trials and may provide the groundwork for standards of reporting 16 .…”
Section: Introductionmentioning
confidence: 99%